WHO Ear and Hearing Disorders Survey: Ecuador National Study 2008-2009. (27th April 2014) - Ullauri, Alejandra; Smith, Andrew; Espinel, Mauricio; Jimenez, Carlos; Salazar, Cesar; Castrillon, Rodrigo
Abstract : Objectives . (1) Provide regional governments, institutions, and professionals with local and accurate information on the prevalence of ear and hearing disorders in the Ecuadorian population. (2) Contribute to the global burden of disease by generating standardized data that can be compared among countries and regions. Method . This was a prospective multistage cluster sample design study. Population tested included all members of households selected according to the sample strategy (cluster sample design). Testing was carried out in hospital facilities across the country including audiometry/TEAOEs and otological examination. Results . 5762 subjects were tested, with a global prevalence of hearing disability of 5% with a 95% CI of 3.9% a 6.1%. Out of the total population tested 14.52% are in need of action or services. Conclusions . The prevalence of disablility in hearing correlates with the prevalence found in other studies using the same protocol. The Ecuadorian population is in need of a substantial improvement in hearing services delivery.